PENGKAJIAN IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DI SEKOLAH DASAR DAN MADRASAH ffiTIDAIYAH DI PROPINSI DAERAH ISTIMEWA YOGYAKARTA - Suryono, Yoyon; Raharja, Setya (LPMPP Universitas Negeri Yogyakarta, 2003)
This article is based on a research with a diagnostic evaluationsurvey approach conductedto obtain a description of theimplementationof the school-based management (SBM) at Islamicprimary schools and primary schools with no special religiousaffiliationin the Yogyakarta Special Priovince. with the YogyakartaMunicipality andthe Sleman and Kulon Progo Regencies.represented respectively bythe Gondokusuman. Depok. and WatesSubdistricts. taken as regional samples and eight state and fourprivate Islamic and non-religiously-affilalted primary schools takenas school samples. Respondents atthe school level consist of theschools' principals. teachers. and students' parents while those at thesubdictrict level consistofschool inspectors, prominent communityfigures. and representativesof subdistrict governing bodies.professional organizations. andthe Department of Religions. Thedata are collected by means of a questionnaire about the schools'condition and implementationof the SBM and analyzed in adescriptive-quantitativeway. The results indicate that the SBM hasstarted to be implemented though still withthe support ofminimummanagerial capability and comprehension.The lack of managerialcapabilityis apparent in the aspects of designing. coordinating,implementing, and evaluatingthe plan or program conducted atschool.The SBM at the state and private Islamic and non-religiously-affiliated primary schools needs to keep beingimplemented to improve school performance and quality and evenlydistribute education,with some improvements in the concept andimplementation. Clearness or clarification of the concept isnecessary to integrate regional autonomy, decentralization ofeducation, and the SBM At the level ofimplementation there need tobe improvements in the mastery ofthe aspects ofthe SBM which atthe moment are still inaccurately understood